Affective heritage and the politics of memory after 9/11 : curating trauma at the Memorial Museum - Micieli-Voutsinas, Jacque (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book critically examines the institutional curation of traumatic memory at the 9/11 Memorial Museum and its evocative power as a cultural storyteller. Memorial Museums are evocative spaces. Drawing on aesthetic practices deeply rooted in representing the 'unrepresentability' of cultural trauma, most notably the Holocaust, Memorial Museums are powerful, popular mediums for establishing cultural values, asking the visitor to contemplate "Who am I?" in relation to the difficult histories on display. Using primary data, this book poses important questions about the emotionally-charged site: what 'moral lessons' are visitors imparted with at the 9/11 Memorial Museum? Who is the cultural institution's primary audience-the imagined community it reconstructs this traumatic history and safeguards its memories for? What does the National September 11 Memorial & Museum ultimately teach visitors about history, ourselves, and others?"--
Manic memories, contested meanings of place -- Affective pedagogies, emotional learning -- Trauma after 9/11 : Holocaust Memorial lessons -- 9/11 memory and the "trauma economy" -- Conclusions : Towards non-violent archives of 9/11 memory -- Epilogue: Affective heritage and 9/11 memory in the age of Trump.
OCLC-licensed vendor bibliographic record.
Keywords: National September 11 Memorial & Museum (Organization); Historical museums -- Social aspects -- New York (State) -- New York; Memorials -- New York (State) -- New York -- Psychological aspects; Memorialization -- United States; Collective memory -- United States; Psychic trauma -- United States; POLITICAL SCIENCE / General; POLITICAL SCIENCE / History & Theory; POLITICAL SCIENCE / International Relations / General